Physical Activity and Body Mass Index Status of Elderly in Serang Banten Province - Sendy Mohamad Anugrah; Rian Triprayogo; Ida Zubaida; Bimo Alexander (STKIP Muhammadiyah Kuningan, 2021)
Physical inactivity is considered one of the health problems associated with many types of chronic diseases. The level of physical activity is often used as a parameter for monitoring and evaluation of public health. This monitoring is very important because it helps prevent various illnesses, inactivity and decrease mortality rates for the elderly. The purpose of this study was to determine the level of physical activity and BMI of the elderly in Serang City. The research method used is a qualitative descriptive method, involving 84 elderly from Serang and Cipocok Jaya districts in Serang City, Banten Province. The level of physical activity was obtained through the International Physical Activity Questionnaires (IPAQ) questionnaire. The results showed that the elderly in Serang City had low physical activity with a METs value of 438.6 and had a BMI of 26.4 which was in the obese or obese category. the elderly in Kota Serang have low physical activity and are in the category of obesity or overweight. This research can be used as initial data for related institutions regarding the condition of the elderly in Serang so that it can create activities that have a positive impact on the elderly in Serang City.